3D Printing of Biocompatible Supramolecular Polymers and their Composites - Hart, Lewis R.; Li, Siwei; Sturgess, Craig; Wildman, Ricky D.; Jones, Julian R.; Hayes, Wayne (American Chemical Society, 2016)
A series of polymers capable of self-assembling into infinite networks via supramolecular interactions have been designed, synthesized, and characterized for use in 3D printing applications. The biocompatible polymers and their composites with silica nanoparticles were successfully utilized to deposit both simple cubic structures, as well as a more complex twisted pyramidal feature. The polymers were found to be not toxic to a chondrogenic cell line, according to ISO 10993-5 and 10993-12 standard tests and the cells attached to the supramolecular polymers as demonstrated by confocal microscopy. Silica nanoparticles were then dispersed within the polymer matrix, yielding a composite material which was optimized for inkjet printing. The hybrid material showed promise in preliminary tests to facilitate the 3D deposition of a more complex structure.